Efficacy and safety of drug-coated balloon combined with cutting balloon for side branch of true coronary bifurcation lesions: Study protocol for a multicenter, prospective, randomized controlled trial - Wu, Haoyu; Deng, Jizhao; Liang, Lei; Lei, Xinjun; Yao, Xiaowei; Han, Wenqi; Chen, Haichao; Shou, Xiling (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary bifurcation lesions are common of percutaneous coronary intervention (PCI), and the optimal interventional therapy strategy is still a matter of debate and remains a challenge for interventional cardiologists. The provisional stenting technique is still a preferred method for most bifurcation lesions, but restenosis of the side branch (SB) occurs in approximately 17%-19% of cases. Therefore, the dilemma of reducing SB restenosis still exists, and further research on strategies to reduce restenosis for SB is necessary. Drug-coated balloon (DCB) can reduce clinical events in small vessel disease and in-stent restenosis. The efficacy and safety of DCB for SB of true coronary bifurcation lesions have not been fully investigated. A randomized comparison of DCB combined with cutting balloon angioplasty versus cutting balloon angioplasty for SB has never been published. Methods and Design: The purpose of this study is to explore the superiority of DCB combined with cutting balloon versus cutting balloon angioplasty for SB after main vessel (MV) drug-eluting stent implantation of true coronary bifurcation lesions. This study is a multicenter, prospective, randomized controlled trial including 140 patients with true coronary bifurcation lesions. Patients will be randomized in a 1:1 manner to receive either DCB combined with cutting balloon or cutting balloon angioplasty for SB after MV drug-eluting stent implantation. The primary endpoint is the evaluation of late lumen loss (LLL) of SB at the 9-month follow-up. The secondary endpoints include procedural success during initial hospitalization, LLL of MV at the 9-month follow-up, binary angiographic restenosis in MV and SB at the 9-month follow-up, the proportion of patients with a final post-PCI quantitative flow ratio result ≤0.80 for SB at the 9-month follow-up, and major adverse cardiac events during the 24-month follow-up. Conclusions: This clinical trial will provide evidence as to whether DCB combined with cutting balloon for SB of true coronary bifurcation lesions is a superior treatment approach. Trial Registration Number: ChiCTR2000040475. Dissemination: The results of this clinical trial will be published in a peer-reviewed journal.